Pertumbuhan dan Produksi Jagung Manis (Zea mays saccharata Sturt.) Pada Beberapa Persiapan Tanah dan Jarak Tanam - Oimolala Lindungan Larosa hidayat; Toga Simanungkalit; Sengli Damanik (Jurnal Agroekoteknologi, 2015)
Attempts to increase the yield of sweet corn can be done with soil preparation and plant spacing.The purpose of the study was to determine the some appropriate soil preparation and an axact plantspacing to increase the growth and production of sweet corn. The research was implemented in thecommunity land located at Tanjung Sari number 89, Medan with the height of 25 metres above sealevel. began from February until May 2013. The design of the research was a randomized blockdesign factorial with two factors. The first factor was soil preparation (no tillage, minimum tillage,traditional tillage) and the second was plant spacing (20x30, 30x30, 40x30, 50x30 centimeter). Theparameters measured were plant height, diameter of stalk, the weight of root brangkasan , theweight of stalk brangkasan, the weight of leaf brangkasan, the weight of cob brangkasan, the weightof weed dry, net assimilation increase, plant growth increase. The results showed that soilpreparation significantly affected plant height, diameter of stalk, the weight of root brangkasan, theweight of stalk brangkasan, the weight of leaf brangkasan, the weight of weed dry Euphorbia hirtaand the weight of weed dry Cynodon dactylon. Plant spacing significantly affected the weight ofstalk brangkasan, the weight of leaf brangkasan, the weight of weed dry Euphorbia hirta andinteraction significantly affected the weight of cob brangkasan.Keywords : Sweet corn varieties bonanza, soil preparation, plant spacing.